An Appraisal Of Russia and United States of America Involvement in Syrian Civil War, 2011 – 2018 - Praxede C. Egeonu; Joseph Bamidele; Godwin Orakpowenri Orovwiroro (MultiTech Publisher, 2023)
State sovereignty continues to be more abstract in the face of competing powers for national interests. Since the end of WWII, the proliferation of super powers involvements in the domestic affairs of warring nations have become a quandary as the implications of these intrusions become more conspicuous than ever. The study thus interrogates the involvement of Russia and US in the Syrian civil war. The study employed case study research design to interrogate into the phenomenon of Arab spring and used secondary data such as books, research articles, newspapers and government publications in Nigeria. The data collected was content analyzed while the frustration-aggression theory provided the framework of analysis. The study concludes that the Syrian war is a major problem that has altered the course of history for generations to come. The nation has joined a long list of countries that have been ravaged by civil wars and foreign involvements, and no involving nation (Russia and the United States of America) or party have been held accountable for the death, destruction and misery that has plagued Syria and by extension the international community at large. The study thus recommends withdrawal of foreign militias and stopping external support to armed groups opposed to a peaceful, political solution: The withdrawal of foreign militias and financial support for the regime and rebel forces is also an important aspect that requires the cooperation of Russia and the United States of America. Such move should be negotiated under the auspices of the UN.